Phytochemical characterization of the extracts, antioxidant activity, phenolic content and toxicity of the essential oil of Curcuma longa L. - Vera Vera, Jonathan Michael; Dueñas-Rivadeneira, Alex Alberto; Rodríguez Díaz, Joan Manuel; Radice, Matteo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Curcuma longa L. tubers are commonly used as a spice, dye, starch source, and in ancient medicine. Due to its functional properties, extracts and essential oil of C. longa have been used as an antifungal, antimicrobial, antioxidant and anti-inflammatory agent, so it can be an alternative for its potential use in the food industry. Therefore, in this work, the phytochemical characteristics of the extracts, the phenolic content, the antioxidant activity and the toxicity of the essential oil of C. longa were evaluated. The phytochemical characterization of the ethanolic extract was carried out through a phytochemical screening (alkaloids, flavonoids, phenols, saponins, tannins, quinones, resins and reducing sugars) and the extraction of the essential oil by means of hydrodistillation. The determination of the total phenolic content (TPC) was carried out using the Folin-Ciocalteu method; the antioxidant activity with the ABTS and DPPH methods and the oil toxicity by the resazurin reduction method using Escherichia coli as a biosensor. The results obtained in the phytochemical screening indicate the presence of tannins, alkaloids, flavonoids, saponins, quinones and reducing sugars. The total phenolic content (TPC) was 50.99 mg GAE.g-1, the inhibition coefficient (IC50) of the ABTS radical was 426.943 µg.mL-1 and the DPPH radical was 2274.024 µg.mL-1. The mean lethal concentration (LC50) of turmeric essential oil for E. coli was 2585.69 mg.L-1. It is concluded that turmeric essential oil has a high phenolic content, high antioxidant activity and low toxicity for E. coli, which is why it is recommended for use in the food industry.